THE MEANING OF TIKRAR IN THE LEARNING TRADITION IN ISLAMIC BOARDING SCHOOL - Ovi Ramadhani; Rizki Akmalia (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study aims to reveal the meaning of tikrār in the tradition of Qur’anic exegesis (tafsir) learning in Islamic boarding schools (pesantren). Tikrār is understood as a repetitive practice that functions not only to strengthen memory but also as part of the pedagogical culture within the Islamic educational tradition. This research employed a descriptive qualitative approach conducted at Pesantren Ar-Raudlatul Hasanah. Data were collected through observation, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings reveal that tikrār is interpreted as a process of strengthening understanding, internalizing values, and shaping students’ learning culture in Qur’anic exegesis learning. The tradition of tikrār is implemented through repeated explanation of tafsir materials, repeated recitation of verses, murāja‘ah, and continuous learning discussions. These practices shape students’ disciplined, reflective, and knowledge-oriented learning character. This study indicates that tikrār is not merely a repetition method, but a pedagogical tradition that holds significant meaning in tafsir learning within pesantren.